Clinical and molecular profiling of EGFR-mutant lung adenocarcinomas transformation to small cell lung cancer during TKI treatment - Chen, Yongxia; He, Mengye; Dai, Zhengfeng; Wang, Yina; Chen, Jing; Wang, Xiaoting; Dong, Xiao; Huang, Jianfei; Ruan, Jian; Zhang, Xiaochen; Shen, Peng; Jia, Yunlu (Frontiers in Oncology, 2023)
Small cell lung cancer (SCLC) transformation represents a notable mechanism of resistance to tyrosine kinase inhibitors (TKIs) in advanced non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations. To address this clinical challenge, we conducted a retrospective analysis of 1012 cases at Zhejiang University School of Medicine, the First Affiliated Hospital, focusing on patients with EGFR sensitizing mutations.Among this cohort, seven patients exhibited biopsy-confirmed small cell transformation, accounting for 0.7% of cases.Notably, all seven patients were initially diagnosed with stage IV adenocarcinoma (ADC), with four cases classified as poorly differentiated and three as moderately to poorly differentiated ADC. EGFR exon 19 deletions were present in five of these cases. Among the seven cases subjected to next-generation sequencing (NGS), four exhibited mutations in the tumor protein p53 (TP53) gene, while three showed loss of the retinoblastoma1 (RB1) gene. The median duration from the initial diagnosis to small cell transformation was 35.9 months (interquartile range: 12.1-84 months).Following small cell transformation during EGFR inhibition, all patients received etoposide/platinum-based treatment, resulting in a median progression-free survival (PFS) of 4.7 months (interquartile range: 2.7-10.1 months). Notably, most patients in this series had poorly differentiated adenocarcinomas at the outset. Furthermore, TP53 mutations and RB1 loss were common genetic alterations observed in patients with small cell transformation in this cohort, warranting further investigation for the potential association with improved survival outcomes.